Efecto del bioestimulante Kelpak en mezclas con fungicidas químicos para el control de sigatoka negra (Mycosphaerella fijiensis) en banano, en La María. - Gutiérrez Jaramillo, Oswaldo Serafin (2015)
This research was conducted at the " Maria " State Technical University of Quevedo , located at kilometer 7 Quevedo- El Empalme route. Lasted 60 days in de winter season of the year 2014. The overall objective of the research was to evaluate the effect of bioestimulante Kelpak in mixtures with chemical fungicides for control of black sigatoka in banana. And the specific objectives : To evaluate the bioestimulante Kelpak mixed with chemical fungicides in controlling the early stages of the Black Sigatoka disease in banana. Set the lifetime of the sheet with the application of bioestimulante Kelpak , more chemical fungicides for control of black sigatoka in banana determine the emission of leaf area of banana leaf with the application of bioestimulante Kelpak . And make economic analysis to the implementation of bioestimulante Kelpak more chemical fungicides for control of black sigatoka in banana. The answer to this research was determined using a Completely Randomized Design (DCA ) . With 12 treatments, each treatment with 5 floors Banana, where a banana plant represents an experimental unit. Data were analyzed in the INFOSTAT statistical program. In results regarding mixtures opal fungicides, volley, comet gold, Polyram with biostimulante Kelpak, to compare means the application of fungicides opal, volley, comet gold and Polyram, they show no statistical difference between the means. In regard to control sigatoka disease at 56 days were the best treatment 10 comet gold ( 2.96 ), the T5 comet gold + Kelpak (3.04 ), the T1 opal + Kelpak (3, 64 ) e T6 opal (4.04 ) , versus the witness T12 (6.74 ) . As for the best leaf emission what had the T5 comet gold + Kelpak ( 76574.64 ).